Analysis of User Satisfaction with the Digital Scientific Work Catalog System Using the LibQUAL+ Framework - Miftahul Jannah; Asrul Huda; Adri, Muhammad; Dedy Irfan (Universitas Negeri Padang, 2025)
This study investigates user satisfaction with the digital Scientific Work Catalog Information System at Padang State University Library through the application of the LibQUAL+® methodology. The assessment focuses on three core service quality dimensions: Affect of Service, Information Control, and Library as Place. Service quality in academic libraries is a critical determinant of user satisfaction, and understanding its components is essential for guiding future service improvement and innovation. A quantitative approach was employed involving 100 library users, with data collected via structured questionnaires and analyzed using multiple linear regression. The findings reveal that all three dimensions significantly and positively influence user satisfaction, both individually and collectively. Among them, Library as Place demonstrated the strongest effect, emphasizing the continued relevance of physical infrastructure even within digital service environments. These results highlight the strategic need for academic libraries to adopt integrated management approaches that combine technological development, infrastructure enhancement, and staff capacity building. The study contributes to the limited body of research on digital service quality in Indonesian academic libraries and offers a robust empirical model for evaluating user-centered service design. Future research is recommended to explore additional factors such as system usability, cross-institutional validation, and correlations with academic performance using learning analytics.